The fears of judgement effect a question wording effect due to hypothesis confirmation bias - Lehman, Darwin R.; Krosnick, Jon A.; West, Robert L.; Fan,Li (1992)
Three sstudies whether the focus of judgement of a rating scale question can influence responses through a hypothesis confirmation bias. Study 1 showed that focusing the question wording on one of two political parties led non-partisan subjects who had little relevant knowledge to evaluate media coverage as more hostile to that party. Studies 2 and 3 demonstrated that asking for the likelihood that the person was a lawyer. This effect occurred only when a large amount of hypothesis compatible information was available to subjects when they paid close attention to it, and when they had previously been successful t interpreting information as consistent with the hypothesis implied by the question. Together, these studies illustrate two focus of judgement effects and identify factors that regulate their magnitude.
Includes bibliographical references.
Keywords: Confirmation bias; Falsificationism; Verificationism